2019
DOI: 10.1001/jama.2019.16932
|View full text |Cite
|
Sign up to set email alerts
|

Life Expectancy and Mortality Rates in the United States, 1959-2017

Abstract: ife expectancy at birth, a common measure of a population's health, 1 has decreased in the United States for 3 consecutive years. 2 This has attracted recent public attention, 3 but the core problem is not new-it has been building since the 1980s. 4,5 Although life expectancy in developed countries has increased for much of the past century, US life expectancy began to lose pace with other countries in the 1980s 6,7 and, by 1998, had declined to a level below the average life expectancy among Organisation for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
504
1
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 673 publications
(576 citation statements)
references
References 168 publications
19
504
1
8
Order By: Relevance
“…The troubling trend in US CVD mortality, however, is the main culprit for longer-term US life expectancy stagnation. Woolf and Schoomaker (6) recently concluded that drugrelated deaths have played a central role in recent US life expectancy trends, drawing from a rich description of mortality trends and a review of the existing literature, including Ho and Hendi's (5) findings. Woolf and Schoomaker (6) did not perform a formal decomposition of the contributory roles of various death causes, and the authors focused on trends under age 65 y, although mortality dynamics at older ages have also been important for the life expectancy stagnation (7).…”
Section: Discussionmentioning
confidence: 99%
“…The troubling trend in US CVD mortality, however, is the main culprit for longer-term US life expectancy stagnation. Woolf and Schoomaker (6) recently concluded that drugrelated deaths have played a central role in recent US life expectancy trends, drawing from a rich description of mortality trends and a review of the existing literature, including Ho and Hendi's (5) findings. Woolf and Schoomaker (6) did not perform a formal decomposition of the contributory roles of various death causes, and the authors focused on trends under age 65 y, although mortality dynamics at older ages have also been important for the life expectancy stagnation (7).…”
Section: Discussionmentioning
confidence: 99%
“…The implications for public health and the economy are substantial, making it vital to understand the underlying causes." 12 And all of this is occurring in a nation whose healthcare system currently ranks, according the to the World Health Organization, a lowly 37 th in the world. Far from preparing for climate change and what it means, the United States is going backwards, dismantling the fragile system it has.…”
Section: Steven Wolf Of Center On Society and Health Department Of Fmentioning
confidence: 99%
“…After decades of increasing life expectancy in the United States, recent years have shown a stagnation and even a slight decrease (Woolf and Schoomaker, ). Alcohol use has repeatedly been identified as a possible underlying culprit (e.g.…”
Section: Background: Alcohol Use Mortality and Life Expectancymentioning
confidence: 99%